An Error Analysis of Using Simple Past Tense in Writing Narrative Text at Tenth Grade Students of Senior High School 1 Jambi - Sri Ade Fitria; Wennyta Wennyta; Yanti Ismiyati (JELT: Journal of English Language Teaching, 2022)
This study aims to identify whether students make errors and find the types of errors made by students in class X MIPA 1 of Senior High School 1 Jambi City. This research is descriptive qualitative. The subject of this research is X MIPA 1 of Senior High School 1 Jambi City academic year 2021/2022. The data collected through the students' writing test. The results of this study indicate that there are errors made by students in the use of the past tense. All errors in using the past tense have been categorized and identified, namely omission, addition, misformation, and misordering. The findings of this study indicated that there were 102 total errors made by students which are classified into four categories based on the surface strategy taxonomy. There are 14 omission errors, 27 addition errors, 49 forming errors, and 12 sorting errors. The students made a dominant error in misformation. This can be seen from the results of the percentage where the wrong formation is 48.04%, then followed by stacking errors of 11.76%, omissions of 13.73, and addition errors of 26.47%. Based on the results of the study, it can be concluded that the students of class X MIPA 1 SMAN 1 Jambi City made the most types of errors, namely misformation. This misformation error is the most difficult for students because they do not really understand the movement of verbs and the infinitive to the past tense. Students need to practice more in writing narrative texts so that they understand the use of simple past tense and the students can make good narrative texts.